Transcoronary cell infusion with the stop‐flow technique in children with single‐ventricle physiology. Issue 3 (25th March 2018) - Eitoku, Takahiro; Baba, Kenji; Kondou, Maiko; Kurita, Yoshihiko; Fukushima, Yousuke; Hirai, Kenta; Ohtsuki, Shinichi; Ishigami, Shuta; Sano, Shunji; Oh, Hidemasa
Abstract: Background: Almost all reports on cardiac regeneration therapy have referred to adults, and only a few have focused on transcoronary infusion of cardiac progenitor cells using the stop‐flow technique in children. Methods: Intracoronary autologous cardiosphere‐derived cell (CDC) transfer was conducted at Okayama University as a phase 1 clinical trial for seven patients with hypoplastic left heart syndrome between January 2011 and December 2012, and as a phase 2 clinical trial for 34 patients with single‐ventricle physiology between July 2013 and March 2015. Results: A total of 41 patients with single‐ventricle physiology underwent transcoronary infusion of CDC with the stop‐flow technique. The median age was 33 months (range, 5–70 months) and the median weight was 10.1 kg (range, 4.1–16.0 kg). Transient adverse events occurred during the procedure, including ST‐segment elevation or depression, hypotension, bradycardia, and coronary artery vasospasm. All patients completely recovered. There were no major procedure‐related adverse events. In this study, transcoronary infusion of CDC using the stop‐flow technique was successfully completed in all patients. Conclusion: Transcoronary infusion of CDC using the stop‐flow technique in children is a feasible and safe procedure.